Grass Ninja 220 Chopper Machine - Mohammad Noor, Hafsa; Johari, Fahmi Izzudin; Faisol, Hariz Syahmi; Zahir Anuar, Irfan Haziq; Janon, Mohd Najib; Tuan Ibrahim, Tuan Mohd Hafeez Tuan Ibrahim (Multidisciplinary Applied Research and Innovation, 2026)
The Grass Ninja 220 Chopper Machine was developed as a practical solution to real-world challenges faced by small-scale farmers and rural livestock owners, especially in the preparation of animal feed. Traditional grass cutting methods using machetes or sickles are time-consuming, physically exhausting, and produce uneven cuts that affect animal digestion and lead to feed waste. On the other hand, commercial grass chopper machines are often too expensive, heavy, and unsuitable for home-based or small-scale use. To address these challenges, this study proposes a low-cost, compact, and energy-efficient chopper machine made from recycled components, including a 220 W washing machine motor and an 18 plastic bucket as the chopping chamber. The system features a dual-blade configuration with an additional booster blade to enhance internal circulation and cutting efficiency. Several performance tests were conducted, including cutting comparison between wet and dry grass, blade configuration analysis, and one-cycle chopping time. Results showed that the machine consistently produced grass lengths between 2 cm to 5 cm which ideal for goat digestion, with the most efficient and uniform results achieved using the dual-blade and booster blade combination. The machine operated on household electricity, showed minimal vibration, and did not overheat during testing. In conclusion, the Grass Ninja 220 Chopper Machine successfully addresses the issues of manual labor and feed waste, while promoting low-cost, sustainable engineering. Its use of recycled parts, low power consumption, and suitability for local fabrication align with green engineering principles and highlight its potential for community-based agricultural improvement.